Study frequency of the first time C-section and its medical indications in Ardabil city, 2021 - Ghavami, Zahra; Amani, Firouz; Hosseindust, Marzieh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Caesarean section is a surgical intervention to prevent or treat life-threating maternal or perinatal complications but unnecessary caesarean section can put mothers and babies at serious risks. World Health Organization (WHO) recommends a caesarean section rate of about 15 percent or less. Although most countries are trying to stop the increase in caesarean section rates to achieve to the rate proposed by the WHO but in many countries, including Iran, has been much higher. The rate of C-section in Iran has increased from 19.5% in 1976 to about 48% in 2010. This figure has reached 60% in 2013. As repeat caesarean is the most common indication of c-section in Iran, the most practical way to reduce the rate of c-section will be reduction of first-time c-section. Obviously, it is necessary to know indications of first-time c-section to reduce the rate of c section in our country. For this purpose, designing a study to recognize the indications of first-time c-section seems useful. Evaluation of frequency of the first time C-section and its medical indications in Alavi Hospital, in Ardabil, 2021. Methods: In this cross-sectional study, all data of caesarean sections performed in Alavi medical center in 2021 were studied. Among the performed c-sections, all the first caesarean sections were selected and their information and indications were collected. The collected data were entered into Statistical package for social sciences (SPSS) software and analyzed by using tables, graphs, numbers and percentages to evaluate the frequency and indications of first-time c-section. Results: Among all CS performed (2075 patients), 940 mothers, underwent caesarean section for the first time, were included in the study. The frequency of caesarean section for the first time was 45.3%. The mean age of the samples was 27.9 years with a standard deviation of 6.94 years. The minimum age was 14 and the maximum age was 47 years. The number of maternal pregnancies ranged from 1 to 8. Conclusions: The most medical indications for first-time caesarean section with 587 cases (65.7%) and 156 cases (17.5%) were related to fetal distress and lack of labor progression, respectively.